Fire safety evaluation: an alternative method for Brazilian buildings - Hahnemann, André Luiz Coelho; Corrêa, Cristiano; Rabbani, Emilia Rahnemay Kohlman (Revista ALCONPAT, 2017)
With the aim of proposing the legalization of the use of buildings that are subject to restrictions on fire safety legislation in Pernambuco, Brazil, some performance-based fire assessment methods have been described and one of them has been chosen to be applied to two buildings in the city of Recife, proving its effectiveness. As a result, safe and viable solutions have been envisaged, given the restriction for buildings considered as historical heritage or constructed based on previous laws that have been updated. Gretener’s method, if implemented, could become an interesting practice, insofar as it proposes some low cost and safe alternatives without structural interventions, given the international verification of its effectiveness.